Superior hardness–corrosion-resistance combination in a Co-, Cu-modified Ni–Cr–Mo alloy via multiple nanoscale segregation mechanisms. (1st March 2022) - Shima, Haruka; Mori, Manami; Yamanaka, Kenta; Yoshida, Kazuo; Yamazaki, Toshihiro; Chiba, Akihiko
Abstract: Hardening of Ni–Cr–Mo corrosion-resistant alloys facilitates the expansion of their industrial applications; however, it remains challenging. Herein, we report significant hardening in a Co-, Cu-modified Ni–Cr–Mo alloy under appropriate cold swaging/aging conditions. Age-hardening occurred over a relatively short period (∼0.5 h) and became clear upon cold-swaging to an area reduction of ≥60%, exhibiting peak hardness at 500–600 °C. Exceptional hardness (HV599), unattainable in conventional Ni–Cr–Mo alloys, was obtained after aging. Scanning transmission electron microscopy revealed that multiple nanoscale segregation mechanisms, including Suzuki segregation at stacking faults and Cr-rich nanodomains within the severely cold-swaged face-centered cubic matrix, were responsible for the resultant hardening. Furthermore, segregation of Cu, alongside Cr and Mo, along the deformation-induced boundaries induced a fine dispersion of nanoscale Cu precipitates throughout the matrix, imparting further hardening. A superior combination of hardness and corrosion performance was realized through this strategy. Graphical abstract: Image, graphical abstract